Identification of Summer Monsoon Onset over Nepal by using Satellite-Derived OLR Data - Adhikari, Sanjib; Shrestha, Dibas; Nepal, Bikash; Chhetri, Tek Bahadur; Bhattarai, Sadhana (Jalawaayu, 2022)
Summer monsoon onset is considered as the beginning of the rainy season in South Asia. In Nepal, summer monsoon onsets from eastern part and ~80% of the annual rainfall occurs during summer monsoon season (i.e., June to September). The monsoon onset is one of the crucial elements for the socio-economic development as the majority of the population depends primarily on rain fed agriculture systems for their livelihood. For identification of the monsoon onset date over eastern Nepal, daily mean satellite-derived Outgoing Long-wave Radiation (OLR) data (10 × 10 spatial resolution) obtained from National Environmental Satellite Data and Information Service (NESDIS), NOAA is used. Long term OLR data from 1979 to 2019 for March to June is analyzed to study monsoon progression towards eastern Nepal. The rainfall amount obtained from rain gauge stations is compared with the OLR data, which depicts a higher correlation in the southern part of Eastern and Central Nepal than in the northern regions. A convective episode signifies the drop in OLR by about 45 Wm-2 from 10 May to 10 June. Further, the relation between the date of characteristic fall of OLR below 250Wm-2 and monsoon onset date announced by MFD (Meteorological Forecasting Division) for the study period is evaluated to predict new onset dates over the region. The predicted onset date is found as 13th of June on average and its correlation with the MFD onset date is 0.6 (p